Results of the Study of Mining and Processing Plant Waste for the Construction of Motor Roads and Railway Tracks - Valovoi, Oleksandr; Brovko, Dmytro; Afanasiev, Vitalii; Valovoi, Maksym; Popruha, Dmytro (Academic journal Industrial Machine Building Civil Engineering, 2025)
The pavement of technological motor roads consists of rock formations extracted from the quarry. With the current increase in the tonnage of quarry transport, the road pavement structure is also changing. On the other hand, the construction of the railway subgrade on dumps and stripping horizons of the quarry leads to increased operating costs for track repair and maintenance works. The relevant task is to investigate the physical and mechanical properties of rock materials from PJSC “Inhulets Mining and Processing Plant” (InGZK), to develop optimization measures and recommendations for the efficient use of these rocks for technological road pavements and the construction of railway embankments within the quarry and waste dumps of PJSC “InGZK”. The aim of this paper is to study the physical and mechanical properties of the rock formations of PJSC “InGZK” and to determine the grain-size composition of crushed stone produced from dense hard rocks. To determine the physical and mechanical properties of the rock materials of PJSC “InGZK,” the following were sampled: iron ore rock (migmatite) and associated dense rock types such as amphibolites, schists, granites, substandard quartzites, oxidized quartzites, oxidized jaspilites, and arkosic metasandstones. Experimental studies provided the physical and mechanical parameters and data on the grain-size composition of crushed stone from these rocks. Examination of the structure of amphibolites and schists from PJSC “InGZK” showed that these rocks have a dense texture, which provides high strength (1000 and 1200), and their mineral inclusions do not require additional beneficiation. The grains of crushed stone obtained from amphibolites and schists of PJSC “InGZK” have a cubical shape and high void content. This opens up the possibility of their use in the construction of roads and railway tracks, as well as in concrete and reinforced-concrete structures.